(untitled) (Stato, Chiese e pluralismo confessionale, 2018)
SOMMARIO: 1. Il background di una riforma “missionaria” - 2. Insidie ermeneutiche della clausola - 3. Esegesi soggettive e oggettive: limiti applicativi - 4. Una versione mediata: la valutazione sull’appello come indagine de merito causæ - 5. L’applicazione della clausola al processo ordinario … - 6. … e al processus brevior - 7. Considerazioni conclusive. “Si appellatio mere dilatoria evidenter appareat”: some considerations on the sidelines of cann. 1682, § 2 and 1687, § 4 C.i.c. after the motu proprio Mitis Iudex Dominus Iesus ABSTRACT: The paper aims to analyze the problems underlying the clause that states “si appellatio mere dilatoria evidenter appareat”, introduced with the Motu proprio “Mitis Iudex Dominus Iesus” with whom Pope Francis has reformed the processes of marriage nullity in 2015. Beyond the mere terminologic matter, which has also committed the doctrine, given the imperfect clarity of the terms of which the clause is composed, what is at stake is the right of appeal granted to the losing party following a decision “pro nullitate matrimonii”. Legislative innovation must be lowered whithin a broader field of reform, where it’s called to interface with the background of ordinary process and of the new processus brevior, that has the primary goal to chase after the speed-up of processes. The risk of subjectivism in which the judges could fall, focusing on the mere intentions of the appellant subject or on the simple reasons given, and not giving rise to a complete judgment where to reach moral certainty, should be avoided in order to safeguard the aspiration of justice that canon law can not not have, and that precise connotations in terms of faith have only to contribute increasing.